Assessment and determination of 2030 onshore wind and solar PV energy targets of Turkiye considering several investment and cost scenarios - Insel, Mert Akin; Sadikoglu, Hasan; Melikoglu, Mehmet (ELSEVIER, 2022)
The importance of renewable energy (RE) shift increases as the instabilities around the world enhanced by the pandemic raise issues about energy security while the energy demand of countries continue to increase. This is especially the case for Turkiye, which is a member of OECD and among developing countries. In the next decade, onshore wind, and solar photovoltaics (PV) will be the focus of Turkiye's RE sector due to the rapid decrease in their costs. Hence, reasonable estimation of investments to the RE sector and cost projections of onshore wind and solar PV is crucial to plan, decide and set effective energy policies. In this study, three different investment scenarios are generated for RE of Turkiye. In addition, global and local cost projections are conducted for onshore wind and solar PV, again in three different scenarios. These scenarios are then utilized to estimate the annual installed capacity changes of Turkiye. Then, annual installed capacity amounts of Turkiye for onshore wind and solar PV are projected until 2030 in five novel scenarios: Economic, Average, Ambitious, Best-Case, and Worst -Case. According to the results, achievable and the most suitable 2030 targets for onshore wind and solar PV are determined as 25,000 MW and 60,000 MW for Turkiye, respectively. These results will assist the policymakers by elucidating the onshore wind and solar PV future of Turkiye, and the methodology may be useful for determi-nation of RE targets for other countries.
Keywords: Solar PV; Onshore wind; Cost projection; Installed capacity estimation; ELECTRICITY; Engineering